Deletion of Glucocorticoid Receptors in Forebrain GABAergic Neurons Alters Acute Stress Responding and Passive Avoidance Behavior in Female Mice - Scheimann, Jessie R.; Mahbod, Parinaz; Morano, Rachel; Frantz, Lindsey; Packard, Ben; Campbell, Kenneth; Herman, James P. (Frontiers in Behavioral Neuroscience, 2018)
The glucocorticoid receptor (GR) is critically involved in regulation of stress responses (inhibition of the hypothalamic-pituitary-adrenal (HPA) axis), emotional behavior and cognition via interactions with forebrain corticolimbic circuity. Work to date has largely focused on GR actions in forebrain excitatory neurons; however, recent studies suggest a potential role mediated by interneurons. Here, we targeted GR deletion in forebrain GABAergic neurons, including the cortical interneurons, using a Dlx5/6-Cre driver line to test the role of forebrain interneuronal GR in HPA axis regulation and behavior. Our data indicate that GR deletion in GABAergic neurons causes elevated corticosterone stress responsiveness and decreased cross-over latencies in a passive avoidance task in females, but not males. Dlx5/6-Cre driven gene deletion caused loss of GR in interneurons in the PFC and hippocampus, but also in select diencephalic GABAergic neurons (including the reticular thalamic nucleus and dorsomedial hypothalamus). Our data suggest that GR signaling in interneurons is differentially important in females, which may have implications for GR-directed therapies for stress-related affective disease states.